The effects of different parenting styles on self-esteem - Rakel Guðjónsdóttir 2000- (2023)
This study aimed to explore the relationship between university students‘ perceived parenting style in childhood and self-esteem. A sample of 344 Icelandic university students completed the Parental Styles and Dimensions Questionnaire – G1 version (PSDQ-G1) and the Rosenberg Self-Esteem Scale (RSES). The PSDQ-G1 was used to assess participants’ received parenting styles, including authoritative, authoritarian, and permissive. The RSES was used to measure self-esteem. Two hypotheses were tested: (1) individuals raised by authoritative parents would have higher levels of self-esteem than those raised by authoritarian or permissive parents, and (2) the relationship between parenting style and self-esteem would be moderated by the child's gender, with authoritative parenting having a stronger positive effect on self-esteem for males than females. Results revealed that participants who experienced authoritative parenting styles had the highest mean self-esteem score while those who experienced permissive parenting had the lowest. There was no significant gender difference in self-esteem and parenting styles. Studies on the impact of perceived parenting styles on self-esteem are sparse in Iceland, therefore this study contributes to our understanding of the relationship between parenting styles and self-esteem among Icelandic university students Keywords: Parenting styles, self-esteem, university students, PSDQ-G1 Markmið þessarar rannsóknar var að kanna tengsl á milli skynjaðra uppeldisstíla háskólanema og sjálfsálits. Í þessari rannsókn var notast við svör 344 nemenda sem svöruðu Parental Styles and Dimensions Questionnaire – G1 version (PSDQ-G1) and the Rosenberg Self-Esteem Scale (RSES). PSDQ-G1 spurningalistinn var notaður til þess að meta mótekinn uppeldisstíl þátttakenda, leiðandi, stjórnandi og eftirlátan uppeldisstíl. RSES mældi sjálfsálit þátttakenda. Tilgáturnar sem settar voru fram voru (1) einstaklingar aldir upp við leiðandi uppeldi myndu hafa hærra sjálfsálit en þeir sem ólust upp með stjórnandi eða ...